Peran dan Fungsi Pendidik dalam Pengembangan Kurikulum PAI - Testawati, Testawati; Sesmiarni, Zulfani (ALSYS, 2025)
The strategic role of teachers as curriculum implementers positions them as key agents in addressing the dynamics of contemporary education, including the implementation of the Kurikulum Merdeka, the integration of Islamic values, and the reinforcement of 21st-century competencies. This study aims to examine the extent to which teachers’ understanding of curriculum functions influences the effectiveness of the teaching and learning process at MAN 1 Kota Payakumbuh. A quantitative approach was employed using a descriptive-correlational method. Data were collected through a closed-ended questionnaire and analyzed using the Pearson Product Moment statistical technique. The results reveal a very strong and significant relationship between teachers’ understanding of curriculum functions and learning effectiveness, with a correlation value of r = 0.752 and significance level of p < 0.01. These findings indicate that a deep understanding of the structure, objectives, and implementation of the curriculum contributes to the creation of a structured, interactive, and meaningful learning process. Therefore, strengthening teachers' capacity in curriculum comprehension is a strategic step toward improving the quality of education in madrasah settings.